2021
DOI: 10.3389/fnagi.2021.738244
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Blood RGS2 Expression in Mild Cognitive Impairment Patients

Abstract: Regulator of G protein signaling 2 (RGS2) is a gene involved in neuronal plasticity and synaptic signaling, whose expression in the brain is altered in neuropsychiatric and neurodegenerative disorders. Microarray data from large datasets suggested reduced RGS2 mRNA levels in the post-mortem brain tissue and blood of Alzheimer’s disease (AD) patients. The results were previously confirmed by quantitative real-time polymerase chain reaction (qRT-PCR) only ex vivo in lymphoblastoid cell lines derived from AD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Due to the high mortality of STAD [18], it is necessary to find more accurate biomarkers to detect at an early stage and monitor disease progression. According to the prior studies, RGS2 is low-expression in various disease types [19], and identified as a prognostic factor [20]. In our research, we expected to explore the potential mechanism of RGS2 in promoting STAD and its viability as a molecular biomarker.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the high mortality of STAD [18], it is necessary to find more accurate biomarkers to detect at an early stage and monitor disease progression. According to the prior studies, RGS2 is low-expression in various disease types [19], and identified as a prognostic factor [20]. In our research, we expected to explore the potential mechanism of RGS2 in promoting STAD and its viability as a molecular biomarker.…”
Section: Discussionmentioning
confidence: 98%
“…Commonalities in induced gene expression between these tissues would represent a conserved system, which may be detectable in blood [29]. In fact, blood biomarkers have been used in many studies to examine brain health and function [23][24][25][26][27][28][29][30][31][32][33], and while protein biomarkers are most common, RNA biomarkers have also been identified [34][35][36][37][38][39].…”
Section: Of 18mentioning
confidence: 99%